2021
DOI: 10.1016/j.dsp.2021.103058
|View full text |Cite
|
Sign up to set email alerts
|

Unknown uncertainties in the COVID-19 pandemic: Multi-dimensional identification and mathematical modelling for the analysis and estimation of the casualties

Abstract: Insights about the dominant dynamics, coupled structures and the unknown uncertainties of the pandemic diseases play an important role in determining the future characteristics of the pandemic diseases. To enhance the prediction capabilities of the models, properties of the unknown uncertainties in the pandemic disease, which can be utterly random, or function of the system dynamics, or it can be correlated with an unknown function, should be determined. The known structures and amount of the uncertainties can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this regard, recent literature offers insightful perspectives on how to anticipate possible occurrence of future casualties, on which future energy demands and consequently environmental impacts may be related. For example, Tutsoy and co-authors have shown how the use of parametric models for predicting and analysing COVID-19 casualties ( Tutsoy et al, 2021 ; Tutsoy et al, 2020 ), even more when coupled with artificial intelligence techniques ( Tutsoy, 2021 ), can provide insights on how to minimize the impact of restrictive measures during pandemics by considering the multi-dimensional contribution of non-pharmacological policies such as lockdowns, schools’ closure, curfews, etc. Incorporating such knowledge on the complexity of the COVID-19 socio-economic impact mechanisms into the business, industry and public authority policy framework will be key for guiding sustainable energy productions and consumptions in the post COVID-19 era ( Aktar et al, 2021 ; Mofijur et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, recent literature offers insightful perspectives on how to anticipate possible occurrence of future casualties, on which future energy demands and consequently environmental impacts may be related. For example, Tutsoy and co-authors have shown how the use of parametric models for predicting and analysing COVID-19 casualties ( Tutsoy et al, 2021 ; Tutsoy et al, 2020 ), even more when coupled with artificial intelligence techniques ( Tutsoy, 2021 ), can provide insights on how to minimize the impact of restrictive measures during pandemics by considering the multi-dimensional contribution of non-pharmacological policies such as lockdowns, schools’ closure, curfews, etc. Incorporating such knowledge on the complexity of the COVID-19 socio-economic impact mechanisms into the business, industry and public authority policy framework will be key for guiding sustainable energy productions and consumptions in the post COVID-19 era ( Aktar et al, 2021 ; Mofijur et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in real engineering problems, there are systems whose structures, uncertain properties, and all the parameters are unknown. In this case, advanced system identification and signal processing approaches can be developed and optimized with sophisticated approaches [14]. This should be the focus of further research in this paper.…”
Section: Equations Of the Longeron Deformationmentioning
confidence: 99%
“…UAV-based applications can be vulnerable to various threats if the uncertainties are not sufficiently taken into account. Designing a safety radius can be a solution to avoid the risks of collisions [ 98 , 99 , 100 , 101 , 102 ].…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%